Multiple cutaneous melanomas associated with gastric and brain metastases - Lara Caroline Grander; Fernanda Cabral; Alice Paixão Lisboa; Gabrielle Vale; Carlos Baptista Barcaui; Juan Manuel Pineiro Maceira (Sociedade Brasileira de Dermatologia, 2016)
Abstract The occurrence of multiple primary melanomas in a single individual is rare. Most commonly, malignant melanocytic lesions subsequent to the initial diagnosis of melanoma are secondary cutaneous metastases. We report a patient with gastrointestinal bleeding from gastric metastasis of cutaneous melanoma. During clinical evaluation and staging, we discovered a brain metastasis associated with 3 synchronous primary cutaneous melanomas. We suggest the research on the mutation in the cyclin-dependent kinase inhibitor 2A (CDKN2A) (INK4a) in such cases. We also emphasize the importance of clinical examination and dermoscopy of the entire tegument, even after a malignant melanocytic lesion is identified.